Differences in inequality measurement: Ghana case study - Richmond Atta-Ankomah; Monica Lambon-Quayefio; Robert Darko Osei (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Over the years, money-metric measures of inequality such as the Gini coefficient and the Palma Ratio, as frequently used in Ghana, have become useful in providing quantitative measures of welfare distribution that enable a better understanding of the extent and nature of inequality. From these measures, we know that inequality has been rising in Ghana despite high and stable growth and a decline in the poverty rate. Although rising, however, inequality is low in Ghana compared with other countries in the sub-region. In promoting the global understanding of inequality and the distribution of resources for effective policy-making and international cooperation, it is important to monitor and compare inequality across countries. The WIID project is designed to facilitate such a comparison by providing a standardized measure of inequality that is comparable across countries and over time for any given country. Focusing on Ghana, this paper aims to explore the extent to which estimates of Gini coefficients from the WIID Companion are consistent with and add to the prevailing understanding of inequality in Ghana. To this end, we review the primary source of data for the three main Gini series on Ghana (WIID Companion, Ghana Statistical Service, and PovcalNet) in order to highlight data quality issues that affect the comparability of inequality measures over time. We then compare the inequality estimates reported by the WIID Companion with the other two series, highlighting any similarities and interrogating any differences to make an informed commentary on the estimates from the WIID Companion.
Keywords: C81; D31; D63; I32; 330; Gini coefficient; inequality; income; WIID Companion; Ghana